Analysis of the HIV Vaccine Trials Network 702 Phase 2b–3 HIV-1 Vaccine Trial in South Africa Assessing RV144 Antibody and T-Cell Correlates of HIV-1 Acquisition Risk. (27th June 2022) - Moodie, Zoe; Dintwe, One; Sawant, Sheetal; Grove, Doug; Huang, Yunda; Janes, Holly; Heptinstall, Jack; Omar, Faatima Laher; Cohen, Kristen; De Rosa, Stephen C; Zhang, Lu; Yates, Nicole L; et al.
Abstract: Background: The ALVAC/gp120 + MF59 vaccines in the HIV Vaccine Trials Network (HVTN) 702 efficacy trial did not prevent human immunodeficiency virus-1 (HIV-1) acquisition. Vaccine-matched immunological endpoints that were correlates of HIV-1 acquisition risk in RV144 were measured in HVTN 702 and evaluated as correlates of HIV-1 acquisition. Methods: Among 1893 HVTN 702 female vaccinees, 60 HIV-1–seropositive cases and 60 matched seronegative noncases were sampled. HIV-specific CD4 + T-cell and binding antibody responses were measured 2 weeks after fourth and fifth immunizations. Cox proportional hazards models assessed prespecified responses as predictors of HIV-1 acquisition. Results: The HVTN 702 Env-specific CD4 + T-cell response rate was significantly higher than in RV144 (63% vs 40%, P  = .03) with significantly lower IgG binding antibody response rate and magnitude to 1086.C V1V2 (67% vs 100%, P  < .001; P mag  < .001). Although no significant univariate associations were observed between any T-cell or binding antibody response and HIV-1 acquisition, significant interactions were observed (multiplicity-adjusted P ≤ .03). Among vaccinees with high IgG A244 V1V2 binding antibody responses, vaccine-matched CD4 + T-cell endpoints associated with decreased HIV-1 acquisition (estimated hazard ratios = 0.40–0.49 per 1-SD increase in CD4 + T-cell endpoint). Conclusions: HVTN 702 and RV144 had distinct immunogenicity profiles. However, both identified significant correlations (univariate or interaction) for IgG V1V2 and polyfunctional CD4 + T cells with HIV-1 acquisition. Clinical Trials Registration . NCT02968849. Abstract : The immunogenicity profile of HVTN 702 differed from that of RV144. Both identified significant correlations (univariate or interaction) for IgG to V1V2 and polyfunctional CD4 + T cells with HIV-1 acquisition.